Bulgaria : Technical Assistance Report-Bank Supervision. (IMF Staff Country Reports; Country Report, 2019)
This Technical Assistance report on Bulgaria reviews the formalization and implementation of a comprehensive Supervisory and Review and Evaluation Process (SREP) that includes an explicit and detailed supervisory Pillar 2 capital requirement. The paper highlights that unsound banking practices or regulatory breaches cannot be compensated by complementary capital charges. Loan loss provisions and capital charges for loans created as a result of such practices cannot be created and judged on the basis of the common standards. Banking Supervision Department has developed a methodology for the combined risk assessment and subsequent definition of an additional capital requirement for credit risk. Individual outcomes of the top-down stress tests carried out by the Macroprudential Supervision and Financial Stability Directorate can make a valuable contribution to the SREP. It allows the assessment of the quality of internal control in the institution and its capacity to timely produce complete and reliable data. While capital positions globally are adequate, and soundness indicators have improved, partly as a result of the 2016 Asset Quality Review, nonperforming loans remain high in Bulgaria, with notable differences between the banks.